Plasma jet assisted carbonization and activation of coffee ground waste. (December 2020) - Kang, Hongjae; Choi, Seongil; Lee, Jin Hee; Kim, Kwan-Tae; Song, Young-Hoon; Lee, Dae Hoon
Highlights: Feasibility of the production of activated carbon from coffee waste using plasma jet was confirmed. Providing the novel method to produce activated carbon and recovery biomass based on plasma engineering. N2 plasma jet is used for carbonization process and CO2 plasma jet is used for activation process. The characteristic of activated carbon can be regulated based on the plasma treatment conditions. Abstract: Activated carbon has been extensively utilized to adsorb pollutants generated by industrial activities. There have been many attempts to efficiently produce activated carbon from spent coffee grounds in the field of environmental technology. In this study, the feasibility of the novel production of activated carbon from coffee ground waste using a plasma jet was evaluated. A rotating gliding arc generator was designed that used an N2 plasma jet for the carbonization process and a CO2 plasma jet for the activation process. It was confirmed that the coffee ground waste could be carbonized and activated by the two plasma jets in the same reactor. The characteristics of the surface morphologies of the activated carbon samples varied depending on the plasma treatment conditions, such as the electric power of the plasma jet and the treatment time. The results implied that the adsorption capacity of the activated carbon could be optimized by regulating the pore size and distribution based on the plasma treatment conditions with regard to the molecular size of the target adsorbate.